Kinetics and Energetic Parameters Study of Phenol Removal from Aqueous Solution by Electro-Fenton Advanced Oxidation Using Modified Electrodes with PbO2 and Graphene - Abbas, Rowaida N.; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The Electro-Fenton oxidation process is one of the essential advanced electrochemical oxidation processes used to treat Phenol and its derivatives in wastewater. The Electro-Fenton oxidation process was carried out at an ambient temperature at different current density (2, 4, 6, 8 mA/cm2) for up to 6 h. Sodium Sulfate at a concentration of 0.05M was used as a supporting electrolyte, and 0.4 mM of Ferrous ion concentration (Fe2+) was used as a catalyst. The electrolyte cell consists of graphite modified by an electrodepositing layer of PbO2 on its surface as anode and carbon fiber modified with Graphene as a cathode. The results indicated that Phenol concentration decreases with an increase in current density, and the minimum Phenol concentration obtained after 6 h of electrolysis at 8 mA/cm2 is equal to 7.82 ppm starting from an initial concentration about 155 ppm. The results obtained from the kinetic study of Phenol oxidation at different current density showed that the reaction followed pseudo first-order kinetics regarding current density. Energetic parameters like specific power consumption and current efficiency were also estimated at different current density. The results showed that an increase in current density caused an increase in the specific power consumption of the process and decreased current efficiency.